The Influence of Financial Literacy, Pocket Money and Lifestyle on Student Consumptive Behavior on Online Shopping Platforms - Muridno, Danna Gemadigda; Prayitno, Putra Hilmi; Inayati, Ro’ufah; Munir, Syahrul (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
Consumption behavior in the current digitalization era is high because shopping platforms make it easier for everyone to access online shopping through several online shopping platforms. For students, uncontrolled consumptive behavior will burden their finances and cause financial problems to arise in the future. The purpose of this study was to determine (1) the effect of financial literacy on student consumptive behavior on online shopping platforms, (2) the effect of pocket money on student consumptive behavior on online shopping platforms, (3) the effect of lifestyle on student consumptive behavior on online shopping platforms (4 ) the effect of financial literacy, pocket money and lifestyle on student consumptive behavior on online shopping platforms. This study uses descriptive quantitative research with correlational methods using the help of the IBM SPSS Statistics 25 for Windows application program. The population in the study was 136, and in determining the sample using a purposive sampling technique, were 101 respondents in the sample. Data collection for financial literacy used tests for pocket money variables, lifestyle and consumptive behavior using questionnaires. Based on the results of the analysis, it can be concluded that (1) there is an effect of financial literacy on consumptive behavior, (2) there is an effect of pocket money on consumptive behavior, (3) there is an influence of lifestyle on consumptive behavior(4) there is a simultaneous effect of financial literacy, pocket money and lifestyle towards consumptive behavior.